2015
DOI: 10.1128/aem.02712-14
|View full text |Cite
|
Sign up to set email alerts
|

Dysbiosis and Alterations in Predicted Functions of the Subgingival Microbiome in Chronic Periodontitis

Abstract: Chronic periodontitis is an inflammatory disease of the periodontium affecting nearly 65 million adults in the United States. Changes in subgingival microbiota have long been associated with chronic periodontitis. Recent culture-independent molecular studies have revealed the immense richness and complexity of oral microbial communities. However, data sets across studies have not been directly compared, and whether the observed microbial variations are consistent across different studies is not known. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
188
5
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(236 citation statements)
references
References 54 publications
27
188
5
7
Order By: Relevance
“…Oral micriobiome of 25 healthy and 25 chronic periodontitis samples from American population (Kirst et al, 2015) (NCBI Bioproject ID PRJNA269205).…”
Section: Methodsmentioning
confidence: 99%
“…Oral micriobiome of 25 healthy and 25 chronic periodontitis samples from American population (Kirst et al, 2015) (NCBI Bioproject ID PRJNA269205).…”
Section: Methodsmentioning
confidence: 99%
“…The different microbiota clustered either by sampling site, such as the outgroups used as controls for this study (saliva samples in cluster 3 and dentine caries and vagina samples, which are both rich in Lactobacillus, in cluster 4), or by clinical status, such as subgingival samples (healthy samples in clusters 1 and 2 and CP samples in cluster 5). CP sites either can show greater microbial diversity and observed richness, compared with healthy subgingival sites (14,15), or can present no significant difference in microbial diversity, as reported for health versus periodontitis (16). Thus, the large number of samples surpasses the technical variations, at least at the genus level, with the primers used in the different studies, and the difference between periodontal health and disease is larger than the technical variations, as described by Kirst et al (16).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that commensal bacterial species in the oral cavity may function as pathogens in a variety of systemic diseases, including aspiration pneumonia (3) and infective endocarditis (4), as well as having a relationship to pre-term low-weight births (5). Dysbiosis is defined as microbial imbalance, and the term oral dysbiosis has been applied to the association between oral bacterial composition and disorders such as periodontal disease (6) and obesity (7). It has become widely recognized that the gut microbiota is closely associated with health and disease in humans.…”
Section: Originalmentioning
confidence: 99%
“…Similarly, the oral microbiota is also known to change in response to local and general conditions, and is considered to be an indicator of homeostatic deterioration (7,16,17). Although the association between oral and intestinal microbiota is unclear, recent studies have suggested that alterations in the microbial composition of dental plaque are associated with periodontal disease (6,18). In addition, a number of reports have suggested that periodontitis is linked to some systemic disorders, including diabetes mellitus (19,20).…”
Section: Originalmentioning
confidence: 99%